Ks. Franz Scholz i jego posługa kapłańska w Zgorzelcu w latach 1945–1946 - próba nowego spojrzenia - Szpotański, Adam (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2020)
Opinions of Father Franz Scholz about the beginnings of Polish church administration in the so-called Western and Northern Territories arouse controversy. Analysis of previously unknown church documents from 1945–1946 sheds new light on this figure. The documents provide new information on Polish–German relations in the first postwar years. The presented case study concerns situation of German clergymen working in Poland after 1945
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne